Tata kelola sumberdaya pertanian berbasis kelompok tani tanaman pangan di kabupaten Pasaman Barat - Saridin Saridin; Endry Martius; Hasnah Hasnah (IICET (Indonesian Institute for Counseling, Education and Therapy), 2022)
Most of the rural population depend on agriculture for their livelihood. Indonesia is a country that has vast agricultural land. Based on data from the Central Statistics Agency in 2016, for rice fields in Indonesia reached 8.19 million hectares. Population census data shows the number of rural residents is 50.21% (BPS, 2010). West Pasaman Regency from Agricultural Statistics data for five years from 2020 to 2016 has an average planting area of 78,950 hectares of food crops. Great potential in agriculture, of course, this requires the support of agricultural resources for food crops at the farmer group level which are sufficient and easy to obtain to support food crop farming at the farmer group level in West Pasaman Regency. Agricultural resources in the form of internal resources and external resources. Internal resources are all resources that are controlled or owned by farmer groups, while external resources are agricultural resources for food crops originating from outside the farmer groups, namely government resources and private resources. How farmer groups can obtain, use, and how farmer groups can return or account for food crop agricultural resources at the farmer group level in West Pasaman Regency.